2016
DOI: 10.1520/jte20140297
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for the Relationship Between Concentrations of Air Pollutants and Meteorological Parameters in Xi'an, China

Abstract: The current study was based on annual ambient air quality monitoring data and corresponding meteorological observation data of Xi'an in 2011. Distribution models on hourly concentrations of PM10, SO2, and NO2 were studied, and the results showed that statistical distribution functions varied from seasons and from pollutants. The optimal distribution models of PM10 concentrations in the four seasons (spring, summer, autumn, and winter) were generalized extreme value distribution (GEVD), Weibull, Weibull, and GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is easy to see that the simulated values are generally lower than the observed values during various periods. One major reason might be due to the overestimated wind speed (Gao et al, 2015;Tasić et al, 2013), as shown in Figure 6. Another major reason can also account for this phenomenon: the emission Figure 7.…”
Section: The Verification Of the Concentration Fieldsmentioning
confidence: 99%
“…It is easy to see that the simulated values are generally lower than the observed values during various periods. One major reason might be due to the overestimated wind speed (Gao et al, 2015;Tasić et al, 2013), as shown in Figure 6. Another major reason can also account for this phenomenon: the emission Figure 7.…”
Section: The Verification Of the Concentration Fieldsmentioning
confidence: 99%
“…The range of r value = -1 to 1. In general, 0.4 r < suggests poor linear correlation, 0.4 0.7 r ≤ < indicates significant correlation, and 0.7 1.0 r ≤ < stands for highly linear correlation (Gao et al 2016). The lowest value of correlation coefficient r min is calculated according to equation 14and is as follows (Podvezko, Sivilevičius 2013):…”
Section: Designing the Densest Asphalt Mixturementioning
confidence: 99%